AUGMENTED REALITY LABELS FOR TEACHING FACTORY PRODUCT PRESENTATION IN A VOCATIONAL HIGH SCHOOL (MULTIMEDIA PROGRAM) - Herman Thuan To Saurik; Kelvin; Sigit Firdaus Prayogi; Taufikur Rahman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study implements the application of Augmented Reality (AR) on labels or packaging of Teaching Factory (TEFA) SMK Multimedia Program products. An R&D design with a Design Thinking framework (Empathize–Test) was used as a user-centered solution. The prototype was developed using Unity–Vuforia and tested on 55 respondents (50 students and 5 teachers) through questionnaires and observations. Descriptive results show strong support for the feasibility of AR as a presentation medium and practical teaching material. The packaging design results before AR were rated positively with a rating of Good–Very Good at 74.6%. The most appreciated AR element was 3D animation at 85.5%. From a promotional perspective, AR results were perceived as effective–very effective at 81.8%. In the field of vocational education, the description of industrial workflows was considered very comprehensive by the majority at 83.6%, with an adoption interest of 85.5%. The main challenges lie in the application of usability and technical complexity (rated as difficult and very difficult by 60.0%), so improvements to the UI/UX, optimization of 3D asset quality, and the addition of CTA features (buy/location/QR links) are recommended. These findings indicate that the application of AR label technology increases appeal, enriches product understanding, and is relevant as a TEFA project module, while also opening up room for improvement in usability and content pipeline to ensure the sustainability of implementation in vocational learning at SMK Multimedia Program.